Evaluation of the anti-inflammatory potential of Solidago microglossa (Arnica-brasileira) in vivo and its effects on PPARγ activity - RITYELLO S. VOGAS; MARIANA T.M. PEREIRA; LUIZA S. DUARTE; MARA J. CARNEIRO; ANDREW F. FARSURA; JOÃO AUGUSTO M.M. MACHADO; INGRID F. COSTA; MAYARA R.N. TOMÉ; FLORA A. MILTON; FRANCISCO A.R. NEVES; MARCIO ADRIANO ANDREO; BEGOÑA GIMENEZ-CASSINA LOPEZ; et al. (Anais da Academia Brasileira de Ciências, 2020)
Abstract Solidago microglossa is used as an anti-inflammatory agent in traditional Brazilian medicine, and this work evaluated the anti-inflammatory potential of the crude ethanolic extract of the flowers of S. microglossa in vivo, as assayed by paw edema models induced by carrageenan, prostaglandin E2, bradykinin and compound 48/80. In the chemical profile, we identified compounds by electrospray ionization mass spectrometry and quantified them by HPLC-DAD. Additionally, this study analyzed the potential to activate the in vitro transcriptional activity of PPARγ, which is a nuclear receptor linked to the anti-inflammatory response. It was possible to identify five compounds: quinic acid, quercetin, chlorogenic acid, hyperoside, and rutin. In the paw edema evaluation, it was possible to show the potential of reducing edema during the inflammatory process. The crude ethanolic extract of the flowers of S. microglossa activated PPARγ compared to the full agonist rosiglitazone and in a dose-response manner. It is possible to conclude that the extract of the flowers of S. microglossa showed anti-inflammatory activity, and the phenolic compounds present in this species might be responsible for this activity.